O instante da cena do índio: a expressão poética de uma experiência - Andreia Duarte de Figueiredo (2015)
This work aims to show that from experience understood as an event the actor can create artwork in the integrity of his doing. So the research was the analysis of the personal interaction with the indigenous Kamayura and performance of the people in their life. It presents the paths of transposition of this embodiment in operation until the creation of "the Indian scene" in the show "Maritime Ode". It discuss the relationship between the contexts bodies in their significant entirety and the role that these cultural references have in creation. And finally, in a atoral perspective, it positions in the performative theater field, with an actor who wants the possibility to express the poetic form of his experience. The discussions are especially supported by the theory of performance studies, recognizing the knowledge incorporated as a producer of knowledge.